South Asian individuals’ experiences on the NHS low-calorie diet programme: a qualitative study in community settings in England - Chirag Bakhai; Catherine Verity Homer; Maria Maynard; Louisa Jane Ells; Pooja Dhir; Kevin J Drew (BMJ Open)
Background Existing literature examines barriers to the provision of ethnically diverse dietary advice, however, is not specific to total diet replacement (TDR). There is a lack of literature from the UK, limiting the potential applicability of existing findings and themes to the UK context. This study addresses this gap in research by interviewing participants of South Asian ethnicity who have undertaken the National Health Service (NHS) low-calorie diet programme (LCD) for people with type 2 diabetes living with overweight or obesity. This study explores factors that may affect the uptake and acceptability of its TDR, food reintroduction and weight maintenance stages. This aims to provide rich data that can inform effective tailoring of future programmes with South Asian participants.Objective To explore the perspectives of individuals of South Asian ethnicity on an NHS programme using TDR approaches for the management of type 2 diabetes (T2D).Design Qualitative study.Setting Individuals in the community undertaking the NHS LCD programme.Participants Twelve one-to-one interviews were conducted with individuals from a South Asian ethnicity participating in the NHS LCD.Main outcome measures Qualitative semistructured interviews conducted through different stages of the programme. Reflexive thematic analysis was used to analyse the transcripts.Results Key themes highlighted positive and negative experiences of the programme: (1) more work is needed in the programme for person centeredness; (2) it is not the same taste; (3) needing motivation to make changes and feel better; (4) a mixed relationship with the coach; (5) social experiences; (6) culture-related experiences.Conclusion This study provides important experience-based evidence of the need for culturally tailored T2D programmes. Action to address these findings and improve the tailoring of the NHS LCD may improve experience, retention and outcomes on the programme for people of South Asian ethnicity and thereby reduce inequalities.